PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN (Studi pada Bank Milik Bumn yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2014) - Mujariyah "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of capital structure to the financial performance of state-owned banks listed on the Indonesia Stock Exchange 2008-2014 . The ratio of capital structure used is a debit -equity ratio (DER) and financial performance ratios used are return on assets (ROA), return on equity (ROE), and loan-to- debt ratio (LDR). The results showed that the capital structure DER only significant effect on the financial performance of stated owned bank in the review of the ratio of the Loan on deposit ratio (LDR). Keywords: Capital Structure, Financial Performance, Bank Government